Real reading 4 : (Pearson Longman, 2011)
A four-level reading skills series for beginning through advanced students, Real Reading provides students with a meaningful and authentic reading experience. Compelling readings in a variety of genres have been carefully written or adapted from authentic sources and feature a principled approach to vocabulary development.